2016
DOI: 10.1063/1.4945402
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical properties of chlorinated hydrocarbons studied with resonant inelastic x-ray scattering

Abstract: We present a theoretical and experimental study of resonant inelastic x-ray scattering on a large group of chlorinated hydrocarbons: CH3Cl, CH2Cl2, CHCl3, CCl4, CH3CH2Cl, ClCH2CH2Cl, CH3CHCl2, CH3CCl3, C2H2Cl2-iso, C2H2Cl2-cis, C2H2Cl2-trans, and C6H5Cl. Differences in structural and dynamical properties of the molecules generated by diverse chemical environments are observed in the measured Cl(K(α)) spectral maps as well as in the Cl(K) total fluorescence yield spectra. The energy position, relative intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Previous studies have concluded that the initial dissociation dynamics of chlorinated molecules after the 1s ! ⇤ excitation are mostly determined by the coreexcited chlorine and the atom it is connected to (in our case this is always a carbon atom) 29,31,32,62 . The full set of vibrational normal modes were also decomposed and it was shown that the symmetric and antisymmetric C-Cl stretching are the major constituents of the initial movement upon 1s !…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have concluded that the initial dissociation dynamics of chlorinated molecules after the 1s ! ⇤ excitation are mostly determined by the coreexcited chlorine and the atom it is connected to (in our case this is always a carbon atom) 29,31,32,62 . The full set of vibrational normal modes were also decomposed and it was shown that the symmetric and antisymmetric C-Cl stretching are the major constituents of the initial movement upon 1s !…”
Section: Discussionmentioning
confidence: 98%
“…Resonant inelastic X-ray scattering (RIXS) is also a common method for probing dissociation and nuclear dynamics. For chlorinated methanes RIXS has often been used in conjunction with carbon 1s excitation [28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon−chlorine bonds are known to dissociate after excitations to the chlorine first discrete states in chlorinated hydrocarbons. [6][7][8]18 Herein, we present the potential energy surface for the C−Cl chlorobenzene bond dissociation at the IS-CASSCF (8,8) level with the aug-cc-pVDZ-DK basis set, as function of the C−Cl distance, i.e., for a given C−Cl distance, all the other coordinates were optimized. We considered the Cl 1s → σ* and the 1s → π* states, shown in Figure 6, top panel, as well as the ionized state, Cl 1s → ∞ shown in Figure 6, bottom panel.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 99%
“…16,17 On aryl halides, the transition probability to the first σ* state is high, and recent studies have shown that the C−Cl bond photolysis occurs after excitation to this state while the other bond distances of the molecule remain almost the same. 18 Herein, we present an experimental and theoretical study of the photoinduced homolysis of the carbon−chlorine bond in chlorobenzene ice by exposing the condensed film to a monochromatic photon beam centered at the 2822 eV resonant excitation of chlorine and above the ionization threshold of the chlorine K-edge. The photoabsorption leading to the electronic excitations Cl 1s → σ* and 1s → π* has been measured and the hypothesis of free radical coupling reactions was investigated via time-dependent density functional theory and complete active space self-consistent field calculations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The recent development of x-ray sources, as third and fourth generation synchrotrons or x-ray free electron lasers (XFELs), has opened opportunities for investigating new phenomena by means of photoelectron and Auger spectroscopies, electron-ion coincidence techniques, and x-ray emission. [1][2][3][4][5][6] Several processes of high scientific interest are still difficult to measure. This is the case, for instance, of radiative Auger emission 7 and Resonance-Enhanced x-ray Multiple Ionization (REXMI) 8 that would both require the detection of photons not only with high efficiency and resolution but also in coincidence with ions or electrons.…”
Section: Introductionmentioning
confidence: 99%